1993
DOI: 10.1111/j.1751-1097.1993.tb02308.x
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Polyene Aliphatics as Spectroscopic and Mechanistic Probes for Bacterial Luciferase: Evidence Against Carbonyl Product From Aldehyde as the Primary Excited Species

Abstract: The fluorescent alpha-parinaric acid (alpha-PAC) and beta-parinaric acid (beta-PAC) were converted to the corresponding aldehydes and alcohols all of which exhibited absorption and fluorescence properties closely resembling those of the parent acids. alpha-PAC and beta-PAC each binds to luciferase in competition with aldehyde. The hydrophobic nature of the aldehyde site was indicated by the enhanced fluorescence quantum yields of the bound alpha-PAC and beta-PAC. These two polyene acids and the beta-parinaryl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Absorption spectrum of YFP and emission spectra of luciferase bioluminescence and YFP fluorescence. The corrected in vitro bioluminescence spectrum was taken from the report by Cho et al (12)…”
Section: Resultsmentioning
confidence: 99%
“…Absorption spectrum of YFP and emission spectra of luciferase bioluminescence and YFP fluorescence. The corrected in vitro bioluminescence spectrum was taken from the report by Cho et al (12)…”
Section: Resultsmentioning
confidence: 99%
“…Stronger support for this idea would be with more efficient acceptors achieved by having them clearly bound to the Lux. Although the parinaldehydes gave a negative result , an aliphatic aldehyde with an attached fluorophore having absorbance in the range 350–400 nm should work, or alternatively a fluorophore conjugated to the Lux, both of these should produce a complete shift as seen with the natural sensitizers LumP and YFP. That such an alternate proximate acceptor sensitization is feasible is demonstrated with a fusion Lux‐GFP that produced an orange bioluminescence color .…”
Section: Final Thoughtsmentioning
confidence: 99%
“…Cho and coworkers used parinaldehydes, long‐chain aliphatic aldehydes with a fluorescent moiety at the tail end and found no alteration of the normal bioluminescence spectrum. They concluded that this eliminated any excited carbonyl product playing the role of the HEI.…”
Section: Introductionmentioning
confidence: 99%
“…The primary emitting product has been postulated to be the excited singlet-state of the luciferase-hydroxyflavin complex (luciferase-FMNH-OH) formed via the breakdown of the luciferase-flavin peroxyhemiacetal intermediate (luciferase-FMNH-OO-CHOHR). [4][5][6][7][8] The recent results of Lei et al 9 from their study using a new model flavin compound demonstrate clearly that luciferase-hydroxyflavin is the primary emitting product.…”
Section: Introductionmentioning
confidence: 98%